Evidence-based education: Objections and future directions - Dekker, Izaak; Meeter, Martijn (Frontiers in Education, 2022)
Over the past two decades, educational policymakers in many countries have favored evidence-based educational programs and interventions. However, evidence-based education (EBE) has met with growing resistance from educational researchers. This article analyzes the objections against EBE and its preference for randomized controlled trials (RCTs). We conclude that the objections call for adjustments but do not justify abandoning EBE. Three future directions could make education more evidence-based whilst taking the objections against EBE into account: (1) study local factors, mechanisms, and implementation fidelity in RCTs, (2) utilize and improve the available longitudinal performance data, and (3) use integrated interventions and outcome measures.